Military Commanders of the Baltic States Estonia, Latvia, Lithuania, 1918-1940 - Kursietis, Andris J. (Aspekt Publishers, 2018)
The collapse of the Romanov dynasty that had ruled Russia for 300 years created a unique set of circumstances whereby the Baltic States of Estonia, Latvia and Lithuania, which had been part of the Russian Empire, were, in 1918, able to proclaim their independence. This independence was to last only twenty-two years, until 1940, when the Soviet Union occupied all three nations. This book is intended to honor and commemorate the 100th anniversary of the declarations of independence of the Baltic States of Estonia (February 24, 1918), Latvia (November 18, 1918), and Lithuania (February 16, 1918). It provides a brief history of how these nations gained and maintained their independence, and includes biographical information about the senior officers (generals and admirals) of the armed forces during the 1918-1940 period. Forewords to the Latvian and Lithuanian sections of the book were graciously provided by Lieutenant-General Leonids Kalnins, the current Commanding General of the Armed Forces of Latvia, and Lieutenant-General Vytautas Jonas Zukas, the current Commanding General of the Armed Forces of Lithuania